Acoustic Heating Produced in the Boundary Layer - PERELOMOVA, Anna; PELC–GARSKA, Weronika (Archives of Acoustics, 2012)
Instantaneous acoustic heating of a viscous fluid flow in a boundary layer is the subject of investigation. The governing equation of acoustic heating is derived by means of a special linear combination of conser- vation equations in the differential form, which reduces all acoustic terms in the linear part of the final equation but preserves terms belonging to the thermal mode. The procedure of decomposition is valid in a weakly nonlinear flow, it yields the nonlinear terms responsible for the modes interaction. Nonlinear acoustic terms form a source of acoustic heating in the case of the dominative sound. This acoustic source reflects the thermoviscous and dispersive properties of a fluid flow. The method of deriving the governing equations does not need averaging over the sound period, and the final governing dynamic equation of the thermal mode is instantaneous. Some examples of acoustic heating are illustrated and discussed, and conclusions about efficiency of heating caused by different waveforms of sound are made.